Assessing environmental changes in abandoned German vineyards. Understanding key issues for restoration management plans - Rodrigo-CominoJesús; Neumann, Martin; Remke, Alexander; RiesJohannes B. (Hungarian Geographical Bulletin, 2018)
Land degradation in vineyards is a big concern which should be considered by farmers, enterprises and policymakers. Due to intense tillage, the use of herbicides and heavy machinery, vine plantations are registering a decrease in soil fertility and, subsequently, in productivity. Recently, farmers have decided to abandon the vineyards, but any restoration planning is being carried out to recover biodiversity or to reduce soil and water losses. Nowadays, there is no information about environmental changes after the abandonment in terms of possible soil property changes and erosion in Central European vineyards such as in Germany. Therefore, the main aims of this preliminary study were to compare: i) soil properties and soil profiles of one cultivated vineyard and an abandoned one; and, ii) to assess the activation of soil erosion processes using a small portable rainfall simulator. Our results showed that the vineyard registered several differences in soil properties among slope positions and soil profile characteristics due to tillage and trampling effects, showing clear marks of compaction and soil detachment in the lower parts. Also, in this cultivated field, higher means and maxima of soil losses (g m-2) and sediment concentration (g l-1) values than in the abandoned plot were quantified, being the main driving factors the vegetation cover and the inclination. On the other hand, in the abandoned vine plantation, a rapid homogenization of soil profiles and soil properties were found along the hillslope, where a deeper organic horizon was consistently developed above a compacted and rocky horizon, which was generated during the cultivation phase. Due to the high compaction due to the machinery cultivation and the difficulties for the roots to make deep into the soil, the infiltration defaulted and the amount of runoff and runoff coefficient were higher in the abandoned plots than in the cultivated ones.